The role of mental health in primary prevention of sexual and gender-based violence - Aník Gevers; Elizabeth Dartnall (Taylor & Francis Group, 2014)
In this short communication, we assert that mental health has a crucial role in the primary prevention of sexual and gender-based violence (SGBV). However, we found that most research and practice to date has focused on the role of mental health post-violence, and SGBV primary prevention is relying on public health models that do not explicitly include mental health. Yet, key concepts, processes, and competencies in the mental health field appear essential to successful SGBV primary prevention. For example, empathy, self-esteem, compassion, emotional regulation and resilience, stress management, relationship building, and challenging problematic social norms are crucial. Furthermore, competencies such as rapport building, group processing, emotional nurturing, modelling, and the prevention of vicarious trauma among staff are important for the successful implementation of SGBV primary prevention programmes. SGBV primary prevention work would benefit from increased collaboration with mental health professionals and integration of key mental health concepts, processes, and skills in SGBV research.